Mucoadhesive Vaginal Tablets Containing Metronidazole: Screening of Optimal Natural Polymer in the Composition - Kamila Bartoníková; Miroslava Špaglová; Martina Papadakos; Michal Hanko; Oliver Macho (MDPI AG, 2024)
(1) Background: The study aimed to compare the impact of various natural polymers-sodium alginate, acacia gum, carrageenan, guar gum, xanthan gum, and tragacanth on the formulation and the physical properties of mucoadhesive vaginal tablets containing metronidazole (167 mg/g). (2) Methods: The quality of the tablets prepared by direct compression was evaluated by pharmacopoeia tests (uniformity of mass, resistance to crushing, friability). Mucoadhesion of the tablets was characterized by swelling capacity and mucoadhesive strength, i.e., the force required to detach the tablet from the rabbit mucosa. In vitro drug release was performed by a modified dissolution method in paddle apparatus containing the simulated vaginal fluid (pH 4.5). Scanning electron microscopy observed morphological changes on the swollen tablets' surface. (3) Results: Pharmacopoeia tests have shown that all prepared tablets met the requirements on quality. The highest mucoadhesive strength was noted in tablets containing guar and xanthan gum. The highest swelling capacity was possessed by tablets containing carrageenan. (4) Conclusions: Summarizing all tests' results, sodium alginate can be considered the most suitable natural polymer in tablet formulation. The combination of polymers providing higher mucoadhesiveness and at the same time a prolonged release, e.g., xanthan or guar, together with sodium alginate, could also be of interest.